STUDY OF DETERMINING VERTICAL DATUM IN RIVER (CASE STUDY: MUSI RIVER) - Retno Hapsari, Erika
The river is one of the transportation infrastructures that can be used for navigation. Navigation maps require a vertical reference or chart datum that can be used to determine depth and tide predictions. Determination of vertical datum in rivers is more complicated than in the sea because rivers have different characteristics. Also besides, the river flows from upstream to downstream due to differences in altitude. The difference in height along the river waters is not the same, but follows the topographic characteristics of the land around it. This is one of the causes of vertical datum used in rivers changing in stages. In Indonesia alone, there is no standard procedure or procedure for how to determine the river's vertical datum. The purpose of this Final Project is to analyze the determination of vertical datum in river waters so that it can produce several conclusions and suggestions on how to determine the river vertical datum that can be used as input for the government and related agencies. The data used came from two representatives, namely Pushidros TNI-AL and PT. Pelindo II Palembang branch. The method used is harmonic analysis using the admiralty and least square methods. The tidal constant obtained was used to determine the tide type, mean water level, and Z0 value. After obtaining the mean water level and Z0 value, a vertical datum value can be determined by reducing the mean water level by the value Z0. The results obtained are vertical datum values obtained from the same data but using different methods can produce different results. Also, the more extended the observation time will be better because it will increasingly show the characteristics of the river. The least square method is better to use because the results obtained are more accurate.